Help2CARE - Towards a digital platform to help to care for dependent persons and caregivers - Gomes, Nuno (2018)
Nowadays, the training of caregivers and patients in self-care is performed in a health professional-to-patient/caregiver oral communication during consultation or discharge from the hospital, which leads to a limited knowledge retention rate either by caregivers and patients in self-care. The Help2CARE project aims to reduce the high rate of readmissions of patients in hospitals due to the lack of training of their informal caregivers. Therefore, we propose to train these caregivers/self-care patients through the provision of training materials that can increase the level of care provided. For this purpose, we present in this paper the Help2CARE digital platform, consisting of a web application and a mobile application that communicate with each other, which enables training materials to be available to caregivers (according to their patients’ needs of care) in a mobile application. With the web application, it is possible for a health professional to manage caregivers and materials to be made available to them, in order to enable those caregivers to access them through the mobile application, among other features, which enables health professionals to accomplish a closer monitoring of the caregivers under their guidance.